Students’ Motivation in Learning English - Fernanda, Putri; Nasrullah, Rahmat; Faridawati; Maulina; Sain, Yuliyanah; Rachmawati Syarif, Andi (Mataoleo: Journal of English Education and Linguistics, 2025)
This study aims to know the students’ motivation in learning English. The researcher used interview as instrument of the study. The subjects of this research are the students of SMP Kartika Kendari in seven grades on academic year 2022/2023 which consists of 8 students using purposive sampling technique. This research used descriptive study. The researcher focused on the intrinsic motivation which are interest, need, hobby, and goals. The result showed that all the students had high motivation in learning English whether it is because of the interest, need, hobby and goal.